Kajian Bioekologi Pasteuria penetrans - Mulyadi Mulyadi; B. Triman; Bambang Rahayu TP (Jurnal Perlindungan Tanaman Indonesia, 1996)
In bioecological studies of P. penetrans, six experiments were done i.e. study the nematode hosts of P. penetrans; the effect of temperature, soil moisture, spores storage length, soil chemicals (compound  fertilizer, carbofuran, and mancozeb) and methods of application on the pathogenicity of P. penetrans. The research results are as follows:  (1) nematode hosts of P. penetrans are M. incognita, M. javanica, and M. graminicola; (2) temperature tested up to 100oC did not affect on the infectivity of P. penetrans; (3) the highest infectivity of P. penetrans was found on soil moisture 45% than on 0%-30%; (4) spores storage for one, two, and three year after effected the infectivity of P. penetrans; (5) treatment with carbofuran, mancozeb, and compound fertilizer did not affect on the infectivity of P. penetrans; and (6) the used of spores of P. penetrans in grounded tomato roots more effective than in soil and water suspension and more efficient than in soil.